2015
DOI: 10.1681/asn.2014050429
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor C4d Is a Common Denominator in Thrombotic Microangiopathy

Abstract: Complement activation has a major role in thrombotic microangiopathy (TMA), a disorder that can occur in a variety of clinical conditions. Promising results of recent trials with terminal complement-inhibiting drugs call for biomarkers identifying patients who might benefit from this treatment. The primary aim of this study was to determine the prevalence and localization of complement factor C4d in kidneys of patients with TMA. The secondary aims were to determine which complement pathways lead to C4d deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
83
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 31 publications
13
83
0
1
Order By: Relevance
“…Other studies and our unpublished observations have identified glomerular C4d reactivity in biopsies with thrombotic microangiopathy or endothelial injury in a variety of clinicopathologic settings, such as lupus-associated thrombotic microangiopathy, hemolytic uremia syndrome, atypical hemolytic uremia syndrome, and allograft glomerulopathy. [51][52][53] It remains possible that the observed C4d reactivity could represent nonspecific insudative C-4 accumulation (similar to C3 and IgM in focal segmental glomerulosclerosis and/or hyaline), or complement pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies and our unpublished observations have identified glomerular C4d reactivity in biopsies with thrombotic microangiopathy or endothelial injury in a variety of clinicopathologic settings, such as lupus-associated thrombotic microangiopathy, hemolytic uremia syndrome, atypical hemolytic uremia syndrome, and allograft glomerulopathy. [51][52][53] It remains possible that the observed C4d reactivity could represent nonspecific insudative C-4 accumulation (similar to C3 and IgM in focal segmental glomerulosclerosis and/or hyaline), or complement pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 42 renal pathology specimens from 36 patients (28 patients with native kidney disease and 8 patients with renal transplants) with histologically confirmed TMA, C4d deposition (via IHC) was present in ∼88% of samples [83]. Terminal complement complex C5-9 was present in 78.6% samples, C1q was present in ∼92% samples, and MBL in 28.6% samples.…”
Section: Thrombotic Microangiopathymentioning
confidence: 99%
“…Even in patients with a genetic predisposition to aHUS, however, the majority of flares occur after a systemic illness or stressor (61). A recent study reported that C1q and C4d can be seen in the vasculature of most patients with aHUS (62). It is possible that illness or endothelial damage triggers C activation through the CP, but that uncontrolled AP activation perpetuates microvascular injury in susceptible patients.…”
Section: Vasculature and Glomerular Endothelial Cellsmentioning
confidence: 99%